2019
DOI: 10.29278/azd.541157
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Some Physical, Chemical and Microwave Pretreatments on Plum Drying

Abstract: This study was conducted to observe the effects of some physical, chemical and microwave pretreatments on drying period and prune colour of Stanley plums dried in the sun. For this aim, seven pretreatments including piercing with thin needle, cutting fruit layer by knife, microwave application, dipping into solutions of NaOH and K2CO3 with or without olive oil addition were compared with untreated samples. Microwave application was the most effective pretreatment in reducing drying time (95 h) while control wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
3
0
3
Order By: Relevance
“…However, when we look at the literature, there are studies with different moisture values. Li et al 2021 [14] found the moisture values of prunes at 24.16%-24.62%, while Karaat 2019 [33] was 25%, Toğrul and Pehlivan, 2004 [19] determined 15-17%. Although the main reason for the differences between the studies is the targeted dry matter value, it is thought that the ripeness of the fruits, agricultural conditions and climatic changes affect the dry matter value [34].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, when we look at the literature, there are studies with different moisture values. Li et al 2021 [14] found the moisture values of prunes at 24.16%-24.62%, while Karaat 2019 [33] was 25%, Toğrul and Pehlivan, 2004 [19] determined 15-17%. Although the main reason for the differences between the studies is the targeted dry matter value, it is thought that the ripeness of the fruits, agricultural conditions and climatic changes affect the dry matter value [34].…”
Section: Resultsmentioning
confidence: 98%
“…In studies where apple slices were dried with microwave, drying periods were reported as 20, 44, 58 and 138 minutes [36,37]. Stanley variety plum samples, to which physical, chemical and microwave methods were applied as pretreatment, were dried under the sun by Karaat 2019 [33]. In the study conducted that the effect of pretreatment on drying period and plum colour, drying periods were found between 95-401 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Li ve ark. [15] kurutulmuş eriklerin nem değerlerini %24.16-%24.62, Karaat [33] %25, Toğrul ve Pehlivan [18] %15-17 olarak tespit etmişlerdir. Çalışmalar arasındaki farklılıkların temel sebebi hedeflenen kuru madde değeri olmakla birlikte meyvelerin olgunluk durumu, tarımsal koşullar ve iklim değişikliklerinin kuru madde değerini etkilediği düşünülmektedir [34].…”
Section: Bulgular Ve Tartişmaunclassified
“…Toğrul ve Pehlivan [18] erik örneklerine %1 NaOH ile 10-15 saniye bandırma işlemi uyguladıktan sonra güneşte kurutma işlemi ile hedefledikleri nem içeriği olan %15-17 değerine 5 günde ulaşmışlardır. Kimyasal daldırma ön işleminin kuruma süresindeki azalmaya olan etkisi, farklı erik örnekleri ile yapılan çalışmalarda da rapor edilmiştir [10,11,33]. Michalska ve ark.…”
Section: Yarım öRnekler Güneşte Kurutmaunclassified
See 1 more Smart Citation